TREND ANALYSIS USING MANN-KENDALL AND SEN’S SLOPE ESTIMATOR TEST FOR ANNUAL AND MONTHLY RAINFALL FOR SINJAR DISTRICT, IRAQ - ASWAD, FAWAZ KH.; YOUSIF, ALI A.; IBRAHIM, SAYRAN A. (Journal of Duhok University, 2021)
The time series rainfall data of 70 years (1940 – 2010) of Sinjar District used to identify the trend and slope magnitude of this series. To analyze the trend, the non-parametric test (Mann-Kendall test) and Sen’s slope estimator were used. For developing a functional relationship between variables, a linear trend of rainfall data for the studied area evaluated using the linear regression. The annual trend analysis showed decreasing trend because the value of Mann- Kendall’s tau and the magnitude of Sen’s slope estimator were both negative and was found to be - 0.06501 and -0.7283, respectively. Also for the slope of the linear regression was negative and equal to −0.916 mm/year, which represents the rate of decreasing in trend for yearly annual rainfall. In addition, the results showed that the trend analysis of monthly rainfall has a varied trend of rainfall in the rainy months. Finally, the results showed a positive trend (increasing) for the months of October and April and negative trend (decreasing) for the other months.